Long-term Outcomes of the US FDA IDE Prospective, Randomized Controlled Clinical Trial Comparing PCM Cervical Disc Arthroplasty With Anterior Cervical Discectomy and Fusion - Phillips, Frank M; Geisler, Fred H; Gilder, Kye M; Reah, Christopher; Howell, Kelli M; McAfee, Paul C (Spine (Philadelphia, Pa. 1976), 2015)
Prospective, multicenter, randomized clinical trial. To evaluate the long-term safety and effectiveness of the PCM Cervical Disc compared with anterior cervical discectomy and fusion (ACDF) in treatment of patients with symptomatic single-level degenerative spondylosis between C3-C4 and C7-T1 with or without prior cervical fusion. The 2-year results of the PCM Cervical Disc trial have been reported previously. The current study reports the long-term results of the same trial. Patients with single-level cervical spondylosis and radiculopathy with or without myelopathy unresponsive to nonoperative treatment were enrolled. The per protocol patient sample at 5 years included 293 patients (163 PCM, 130 ACDF). Adverse events and secondary surgical procedures are reported on the cohorts through current follow-up, which include 110 patients (68 PCM, 42 ACDF) at 7 years. At 5 years postoperative, all patient-reported outcomes-neck and arm pain visual analogue scale score, neck disability index, and general health (36-Item Short Form Health Survey physical and mental component scores: physical component summary, mental component summary)-were significantly improved from baselines in both groups, and mean scores were significantly better in the PCM group for neck disability index (P=0.001), neck pain (P=0.002), general health (Pphysical component summary=0.014; Pmental component summary=0.004), and patient satisfaction (P=0.005). PCM patients trended toward fewer 2- to 7-year device-related serious adverse events (1/214, 0.5% PCM; 2/190, 1.1% ACDF) and secondary surgical procedures (7/211, 3.3% PCM; 14/290, 7.6% ACDF). Adjacent-level degeneration was radiographically more frequent after ACDF (33.1% PCM, 50.9% ACDF; P=0.006) and was the primary indication for the increase in late-term secondary surgical procedures after ACDF. The long-term results show good clinical outcomes after ACDF and PCM arthroplasty. PCM patients showed greater improvement in neck disability index and neck pain scores with a lower rate of radiographical adjacent-level degeneration and a trend toward fewer secondary surgical procedures. These data support PCM arthroplasty to be a viable and sustainable alternative to ACDF. 1.